“Impuros” e estranhos na Universidade Federal do Tocantins: impasses e perspectivas acerca da sociabilidade de calouros cotistas do Campus Araguaína - Silva, Diêgo Araujo (Universidade Federal do Tocantins, 2016)
The so-called Quota Law on Higher Education - Law No. 12,772 / 12 - provided the students from social class underprivileged the opportunity to coursing an undergraduate degree in federal universities, promoting the inclusion of young people in a totally new environment and often , shoot their socio-cultural reality. Reality that permeated the vicissitudes of contemporary society, whose main engine immediacy of the relationship, causing the construction of an ephemeral individual and fully inserted into the logic of the consumer society. Thus, we analyzed in our work the construction of senses of quota students from entering the university environment and its relationship to contemporary life, the extent to which the consumer society exerts influence on their plans and projects in the university environment. For this we use the categories of "unclean" and "strange" postulated by Zygmunt Bauman because we understand that the quota students for being out of a logic of social order and represent a portion that was subdued and placed on the margins of society, are impure that caused the change of the social order and are the strangers who came to the university climbing spaces and showing visible to other sectors of the academy. We work also with the concepts of youth and consumer society. We used as qualitative research methodology, adopting the focus group and questionnaire as data collection instruments. To analyze the data obtained from the speech of students participating in the research, we used the content analysis technique proposed by Laurence Bardin. From the data obtained verified that the university entrance promotes the student unitholder changes in the way that maintains and builds social relationships inside and outside the academy, mainly because this student comes into contact with a range of opportunities that previously had no access. The sense of being university is to the extent that it considers the social space of the university as an environment that provides them with knowledge, critical and personal growth. Moreover, according to a student who seeks, at all times, forms of legitimization and constitution of its identity within the university. Insofar as they encounter all clothing contrary to the proposal of the quota system, these young people forged identity construction mechanisms fostered within the environment itself to which they relate. Yet we find that for the shareholders, the vicissitudes of contemporary life have all had their influence on the lives of the young, since all the time suffering the onslaughts of market society which require the subject to the need to take advantage of assets that give the false him feeling of pleasure, or pleasure fluid, shattered.